Implementasi Aplikasi Smart Asset dalam Memanfaatkan Teknologi Informasi Komunikasi Sebagai Sarana Peningkatan Tata Kelola BUMDes dan Industri Rumah Tangga Untuk Memajukan Perekonomian Desa Pagerwangi kec. Lembang kab. Bandung Barat di Era Adaptasi Kebias - Wahab Sya’roni, Deden Abdul; Puspitawati, Lilis; Supriyati, Supriyati; Dwi Yulianto, Hery; puti purfini, apriani; Bahri, Ramadhan Syaeful (Program Studi D3 Komputerisasi Akuntansi Fakultas Teknik dan Ilmu Komputer , Universitas Komputer Indonesia, 2021)
a follow-up to the superior community empowerment program of Indonesian computer universities (PPMUPT) which consists of a collaboration of 3 study programs, namely the Postgraduate Program, Accounting and Computerized Accounting, in the 2nd year PPMUPT Program funded by the Ministry of Research, Technology and Higher Education, as part of the tridarma has begun implemented after the adaptation of new habits / new normal with mentoring meetings on a limited scale, starting again in accordance with the programs that have been launched by the Village-owned enterprises in Desa Pagerwangi, West Bandung Regency. Assistance includes the need to improve BUMDES by utilizing existing facilities and those that are being prepared. Assistance for BUMDes optimization in terms of ICT utilization, BUMDes governance in terms of strengthening HR competencies, financial management and marketing of IRT products that are integrated and facilitated in BUMDes. is in the process of making the BUMDes e-ticket, e-commerce and postal (point of sale) application which is integrated with the BUMDES SMART ASSET that has been built and improved according to the BUMDes Desa Pagerwangi work program in 2020. In addition to this, an online training system is implemented and direct assistance in BUMDes between lecturers, village officials, IRT and other communities while still following health and social distancing procedures. The results of the activities obtained by the PPMUPT UNIKOM implementation team in 2020 found other potentials that could be developed in the Village such as the establishment of the Village Multipurpose Building which can be used for various activities / meetings with the Village community (giving BLT, Village Deliberations, receptions, seminars etc.) , Village sports field facilities (Sorga Desa) which can be used as an integrated tourist site (camping ground, jogging track, café, and minimarket) and the construction of BUMDES Building which has been facilitated with adequate facilities has been completed. Having sufficient village potential and balanced with good management is expected to help the village from an economic downturn after the covid-19 outbreak.